THE REPRESENTATION OF CONSUMER GREEN PURCHASE INTENTION IN THE VALUE OF GREEN PRODUCT QUALITY AND GREEN BRAND IMAGE ON CUSTOMERS AT THE BODY SHOP TEA PRODUCTS IN SOUTH TANGERANG - Sari, Ade Ratna; Gursida, Hari; Wihartika, Doni (Yayasan Education and Social Center, 2025)
This study aims to examine the influence of green product quality and green brand image on the green purchase intention of consumers of The Body Shop products in South Tangerang City. The research method used is a qualitative approach with in-depth interview techniques with The Body Shop customers who are environmentally conscious. The results of the study indicate that positive perceptions of the quality of natural and certified green products and a strong and environmentally responsible brand image contribute significantly to shaping consumers' green purchase intentions. Social and emotional factors also play a major role in supporting green purchasing decisions, where consumers feel that purchasing green products is an expression of self-identity and social responsibility. Although product prices tend to be higher, consumers who are already aware of the value of sustainability are still willing to pay a premium price. This study provides important implications for business actors in developing green marketing strategies with a focus on improving product quality and strengthening green brand images in order to increase the purchase intentions of consumers who are increasingly concerned about the environment.